Visibility regimes in mediatized publicness - Mateus, Samuel (2014)
Considering the relationship between politics, media and publicness, this paper ponders the consequences of visibility in the political field. Identifying some of its existing regimes, it will posit that today visibility plays an ambivalent function to politics: it can simultaneously operate as a synoptic monitoring and control of politicians; and at the same time it may stand as an opportunity to build a charismatic leadership. In fact, political visibilities are now negotiated between the boundaries of private and public realms, and they can take the form of a risk, or an opportunity to build on a charismatic leadership.